Smoking enhances the expression of angiotensin‐converting enzyme 2 involved in the efficiency of severe acute respiratory syndrome coronavirus 2 infection. (2nd November 2022) - Suzuki, Rigel; Ono, Yuki; Noshita, Koji; Kim, Kwang Su; Ito, Hayato; Morioka, Yuhei; Tamura, Tomokazu; Okuzaki, Daisuke; Tagawa, Tetsuzo; Takenaka, Tomoyoshi; Yoshizumi, Tomoharu; Shimamura, Teppei; et al.
Abstract: Smoking is one of the risk factors most closely related to the severity of coronavirus disease 2019 (COVID‐19). However, the relationship between smoking history and severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infectivity is unknown. In this study, we evaluated the ACE2 expression level in the lungs of current smokers, ex‐smokers, and nonsmokers. The ACE2 expression level of ex‐smokers who smoked cigarettes until recently (cessation period shorter than 6 months) was higher than that of nonsmokers and ex‐smokers with a long history of nonsmoking (cessation period longer than 6 months). We also showed that the efficiency of SARS‐CoV‐2 infection was enhanced in a manner dependent on the angiotensin‐converting enzyme 2 (ACE2) expression level. Using RNA‐seq analysis on the lungs of smokers, we identified that the expression of inflammatory signaling genes was correlated with ACE2 expression. Notably, with increasing duration of smoking cessation among ex‐smokers, not only ACE2 expression level but also the expression levels of inflammatory signaling genes decreased. These results indicated that smoking enhances the expression levels of ACE2 and inflammatory signaling genes. Our data suggest that the efficiency of SARS‐CoV‐2 infection is enhanced by smoking‐mediated upregulation of ACE2 expression level.